A broadband polarization splitter directional coupler based on tilted subwavelengh grating metamaterials - Luque-González, José Manuel; Herrero-Bermello, Alaine; Ortega-Moñux, Alejandro; Sánchez-Rodriguez, Marina; Velasco, Aitor V.; Schmid, Jens H.; Cheben, Pavel; Molina-Fernández, Íñigo; Halir, Robert (My University, 2020)
Tilted subwavelength gratings (SWG) allows anisotropy tailorable metamaterials with applications in polarization management. Based on this concept, here we experimentally demonstrate a broadband directional-couplerbased polarization beam splitter with sub-decibel insertion loss in a 100 nm bandwidth.
Keywords: Silicio sobre aislante; Sistemas de comunicación inalámbricos; Fotónica; Metamateriales; Polarización; Circuitos integrados-Diseño y construcción; silicon photonics; silicon-on-insulator subwavelength gratings; metamaterials; Polarization management; SWG